LOCATION OF ADDITIONAL LIBRARY FACILITY IN BEREKUM MUNICIPALITY USING BERMAN AND DREZNER ALGORITHM - Editor, Section; Kusi, Prince; Twumasi, Eric Appiah-Twumasi; Darkwah, Professor (Journal of Statistics and Actuarial Research, 2021)
Purpose: To model location of an additional library facility in the Berekum Municipality as a conditional p-center problem which will serve as a reference centre for Schools and Colleges within the municipality Methodology: The data for this study was the road distance between the suburbs of Berekum Municipality. The suburbs of the municipality were coded and Floyd's algorithm was used to find the distance matrix, d (i, j) for all pairs shortest path. Subsequently, the Researchers used Berman and Drezner's algorithm on 18-nodes network which had two existing library facilities in Berekum and Jininjini to locate additional Library facility for Library users in Berekum Municipality. Matlab program software was used for the coding of the Floyd-Warshall algorithm. The codes for Floyd-Warshall algorithm was developed and ran on DellAMD Athlon (tm) II P360 Dual-Core Processor 2.30GHz of RAM 3.00GB, 64-bit Operating System with Windows Ultimate Laptop Computer Results: The analysis of the study revealed that, an additional library facility using Berman and Drezner (2008) should be located at Akrofro with an objective function value of 8. The results obtained from the study is useful to locate a public library facility that will benefit all the people in Berekum municipality. Specifically, the results revealed the new public library facility to be built in Berekum Municipality should be sited at Akrofro. Unique contribution to theory, practice and policy: The implication of the results is that the minimum distance travelled by the farthest library user to the new library facility at Akrofro is 8 kilometres. Stakeholders should adopt the use of Berman and Drezner's algorithms in establishing facilities such as markets, hospitals, recreational centres and so on